2017
DOI: 10.18632/oncotarget.22839
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb protein RING1A limits hematopoietic differentiation in myelodysplastic syndromes

Abstract: Genetic lesions affecting epigenetic regulators are frequent in myelodysplastic syndromes (MDS). Polycomb proteins are key epigenetic regulators of differentiation and stemness that act as two multimeric complexes termed polycomb repressive complexes 1 and 2, PRC1 and PRC2, respectively. While components and regulators of PRC2 such as ASXL1 and EZH2 are frequently mutated in MDS and AML, little is known about the role of PRC1.To analyze the role of PRC1, we have taken a functional approach testing PRC1 compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In fact, we found that this mark strongly co-localized with H3K27me3 at Ezh1 core TG in Ezh1 +/- Ezh2 Δ/Δ HSPCs ( Figure 7 B). Intriguingly, inhibition of Ring1A, an enzymatic component of PRC1, has been shown to have an antitumor effect on an MDS cell line and primary CD34 + cells from patients with MDS ( Palau et al., 2017 ). Therefore, the functional inhibition of PRC1, especially variant PRC1, would represent an interesting approach to eradicate MDS stem cells by inducing the de-repression of Ezh1 core TG in Ezh2 -insufficient MDS.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we found that this mark strongly co-localized with H3K27me3 at Ezh1 core TG in Ezh1 +/- Ezh2 Δ/Δ HSPCs ( Figure 7 B). Intriguingly, inhibition of Ring1A, an enzymatic component of PRC1, has been shown to have an antitumor effect on an MDS cell line and primary CD34 + cells from patients with MDS ( Palau et al., 2017 ). Therefore, the functional inhibition of PRC1, especially variant PRC1, would represent an interesting approach to eradicate MDS stem cells by inducing the de-repression of Ezh1 core TG in Ezh2 -insufficient MDS.…”
Section: Discussionmentioning
confidence: 99%
“…Using PRT4165 an pharmacological inhibitor of RIN1G1B, we have shown that in differentiating human pluripotent stem cells, RING1B and BMI1 are repressors of ectoderm specification. We hereby report the effect of PRT4165 induced inhibition hESC growth and differentiation, while all the previous reports been performed on cancer cell lines (Palau et al, 2017) as well as mice/rat models (Eliades et al, 2016). Although Ring1b knockout studies have unraveled the indispensable functions of Ring1b protein during murine development and these studies are crucial, in reality subtle changes in certain proteins generate interesting outcomes, and hence we used an inhibition approach to study function of RING1B in lineage specification, also no studies on effect of its inhibition in human ES cells have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that PRT4165 though is catalytic activity inhibitor of RING1B, yet is caused reduction at the transcript and protein level. Palau et al (2017) showed that when SKK‐1 (cell line derived from adult acute leukemia cells) was treated with PRT4165 there was reduction of RING1B and BMI1 at protein level. Although we do not have a mechanism to explain, such observation has been previously reported where a histone modifier activity inhibitor has also led to reduced expression of histone deacetylases at RNA and protein level (Krämer et al, 2003, Yang et al, 2015, Cai et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the key role of this epigenetic regulator in the pathogenesis of MDS. However, RING1A pharmacological inhibition affects the stem cell compartment in both MDS patients and healthy donors, hampering its clinical applicability (Palau, Garz et al 2017). The Buschbeck group applies genetic screening methods (Fellmann, Hoffmann et al 2013) and cell culture models to identify chromatin regulators able to increase the response to the nucleoside-analogue azacitidine.…”
Section: Polycomb Group Proteins In Cancermentioning
confidence: 99%